INFLUENCE JOB TRAINING AND TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE MEDIATED BY WORK ENGAGEMENT UD. Ony - Fitri Rezeki; Hamzah M Mardi Putra; Supriyanto Supriyanto; Dewi Kurniasih; Tri Ngudi Wiyatno (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to examine the influence of Training and Transformational Leadership on Employee Performance through the mediating role of Work Engagement. The research employs an explanatory quantitative approach with a causal design, using a structural model to test the relationships among variables. Data were collected from 68 employee respondents selected through purposive sampling and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings show that all constructs—Training, Transformational Leadership, Work Engagement, and Employee Performance—meet the criteria for reliability and validity. The values of Cronbach’s Alpha, rho_A, Composite Reliability, and AVE are above the established thresholds, confirming that the measurement instruments are both consistent and valid. Furthermore, the R Square results indicate that Work Engagement (R² = 0.820) and Employee Performance (R² = 0.722) are strongly explained by the predictor variables, emphasizing the significant role of the independent variables in influencing the outcomes. Model fit indices, including SRMR, d_ULS, d_G, Chi-square, and NFI, demonstrate that the Estimated Model is consistent with the Saturated Model, thereby confirming the adequacy of the proposed structural model. Overall, the study concludes that the developed model is valid, reliable, and demonstrates a good level of fit, providing strong empirical evidence for the relationships among Training, Transformational Leadership, Work Engagement, and Employee Performance.